Social functionality, perceived wellness and coping with stress in individuals with substance use disorder - Kargın, Maral; Hiçdurmaz, Duygu (Journal of Dependence, 2018)
Substance use disorder is an important public health problem spreading rapidly all over the world. Substance use disorder, a brain disease, continues with remissions and relapses. It can cause a wide variety of medical problems, disruption of social functioning, loss of productive years of life, and even death. Individuals who can not fully fulfill their social functioning prefer to be together and use substances with individuals who use substance like themselves by isolating themselves from society. The vicious cycle that occurs in this way causes the individual’s wellness and theirs perception of this wellness to be adversely affected and individuals to lose their well-being status. The individual who perceives his / her abstinence negatively prefer to use the substance as a method of coping to feel good. It is possible that this problem can be solved and the positive results can be reached in the treatment, but only by fighting relapse. In this struggle, complementary multidisciplinary team work and nurses in this team; identification of risk groups, evaluation of individuals with substance use disorders as a whole are very important in continuity of the care. In this context, psychiatric nurses can protect the hopes of the individuals and integrate the information obtained through evidence to their practices while performing the roles of education and counseling.